The Efficacy of a Compassion-Focused Therapy–Based Intervention in Reducing Psychopathic Traits and Disruptive Behavior: A Clinical Case Study With a Juvenile Detainee. (October 2019) - Ribeiro da Silva, Diana; Rijo, Daniel; Castilho, Paula; Gilbert, Paul
Conduct disorder (CD) is the most diagnosed psychopathological disorder in juvenile detainees. The presence of a CD diagnosis, especially when associated with psychopathic traits, contributes to a poor prognosis, high recidivism rates, and low responsivity to treatment in these youth. Although group intervention programs have proven to be effective in decreasing antisocial behavior, studies testing their efficacy in reducing psychopathic traits are scarce and limited. Moreover, there is a lack of research focused on the efficacy of individual treatment approaches specifically designed to reduce psychopathic traits and disruptive behavior in juvenile detainees. Compassion-focused therapy (CFT) shows promising results in the treatment of several psychopathological disorders. Besides, there is some theoretical support to consider CFT a suitable approach to treating juvenile detainees. However, there are no treatment programs based on CFT that are designed to target psychopathic traits and disruptive behavior in these youth. Consequently, treatment outcome research in this area is absent. This clinical case study presents the treatment of a juvenile detainee with CD, a high psychopathic profile, and a very high risk for criminal recidivism using the PSYCHOPATHY.COMP program (a 20-session individual CFT program), which was specially designed to reduce psychopathic traits and disruptive behavior. The treatment outcome data revealed a significant reduction in psychopathic traits and disruptive behavior. The treatment gains were maintained and/or increased over time (3 months after program completion). This clinical case study demonstrates the feasibility and efficacy of the PSYCHOPATHY.COMP program in reducing psychopathic traits and disruptive behavior in a juvenile detainee.